2015
DOI: 10.1177/0884533615591057
|View full text |Cite
|
Sign up to set email alerts
|

Management of Hyperglycemia and Enteral Nutrition in the Hospitalized Patient

Abstract: There has been increased attention on the importance of identifying and distinguishing the differences between stress-induced hyperglycemia (SH), newly diagnosed hyperglycemia (NDH), and hyperglycemia in persons with established diabetes mellitus (DM). Inpatient blood glucose control is now being recognized as not only a cost issue for hospitals but also a concern for patient safety and care. The reasons for the increased incidence of hyperglycemia in hospitalized patients include preexisting DM, undiagnosed D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 62 publications
0
41
0
9
Order By: Relevance
“…Hyperglycemia is almost universally observed in critically ill patients contributing to poor clinical outcomes. EN formulas worsen hyperglycemia and may hinder efforts at controlling glucose . Increasing awareness of the problems associated with standard nutrition has prompted investigators to explore alternative options, including the substitution of high‐glycemic to low‐glycemic carbohydrates, addition of lipids as an energy source, or allowing an energy deficit through hypocaloric nutrition or permissive underfeeding …”
Section: Discussionmentioning
confidence: 99%
“…Hyperglycemia is almost universally observed in critically ill patients contributing to poor clinical outcomes. EN formulas worsen hyperglycemia and may hinder efforts at controlling glucose . Increasing awareness of the problems associated with standard nutrition has prompted investigators to explore alternative options, including the substitution of high‐glycemic to low‐glycemic carbohydrates, addition of lipids as an energy source, or allowing an energy deficit through hypocaloric nutrition or permissive underfeeding …”
Section: Discussionmentioning
confidence: 99%
“…Before beginning enteral nutrition, it is important to know the metabolic status, previous control of diabetes, and insulin requirements. [29] Continuous enteral nutrition has an effect, not totally known, in secretion and action on incretin hormones and can contribute to hyperglycemia. Hospitalization produces insulin resistance and together with delivery of glucose and gluconeogenic substrates via enteral contribute to hyperglycemia.…”
Section: Nutritional Supportmentioning
confidence: 99%
“…Although some institutions do not have recommendations about this, [31] diabetic-specific formulas have been suggested in patients with persistent hyperglycemia. [29] Retrospective studies with different insulin regimens have demonstrated effectiveness to manage hyperglycemia with a variable degree of control. These studies use basal insulin glargine once daily, NPH every 4 or 6 hours, or 70/30 biphasic insulin twice or 3 times a day.…”
Section: Nutritional Supportmentioning
confidence: 99%
“…Uma menor oferta calĂłrica em pacientes internados em UTI estĂĄ associada ao aumento nos episĂłdios de hipoglicemia (28)(29)(30) , infecçÔes severas (31) , maior tempo de internação (32) , maiores gastos com a saĂșde desses indivĂ­duos (33) e aumento nas taxas de mortalidade (31,34) . O consenso canadense para terapia nutricional em paciente crĂ­tico preconiza que o acompanhamento diĂĄrio e o rĂ­gido controle do protocolo de nutrição enteral da UTI por parte da EMTN deve facilitar um maior recebimento da dieta prescrita (35) .…”
Section: Discussionunclassified